Wnt-5a Signaling Mediates Metaplasticity at Hippocampal CA3-CA1 Synapses in Mice - Parodi, Jorge; Mira, Rodrigo G.; Fuenzalida, Marco; Cerpa, Waldo; Serrano, Felipe G.; Tapia-Rojas, Cheril; Martinez-Torres, Ataulfo; Inestrosa, Nibaldo C. (My University, 2024)
Wnt signaling plays a role in synaptic plasticity, but the specific cellular events and molecular components involved in Wnt signaling-mediated synaptic plasticity are not well defined. Here, we report a change in the threshold required to induce synaptic plasticity that facilitates the induction of long-term potentiation (LTP) and inhibits the induction of long-term depression (LTD) during brief exposure to the noncanonical ligand Wnt-5a. Both effects are related to the metaplastic switch of hippocampal CA3-CA1 synaptic transmission, a complex mechanism underlying the regulation of the threshold required to induce synaptic plasticity and of synaptic efficacy. We observed an early increase in the amplitude of field excitatory postsynaptic potentials (fEPSPs) that persisted over time, including after washout. The first phase involves an increase in the fEPSP amplitude that is required to trigger a spontaneous second phase that depends on Jun N-terminal kinase (JNK) and N-methyl D-aspartate receptor (NMDAR) activity. These changes are prevented by treatment with secreted frizzled-related protein 2 (sFRP-2), an endogenous antagonist of Wnt ligands. Here, we demonstrate the contribution of Wnt-5a signaling to a process associated with metaplasticity at CA3-CA1 synapses that favors LTP over LTD.
Keywords: noncanonical wnt signaling; wnt-5a; calcium; metaplasticity; hippocampus